Effect of Different Adhesive Systems on Shear Bond Strength Between Resin Cement and Titanium Abutment Surfaces - İrem Sözen Yanık; Dilara Sahin Hazir; Barış Güncü (Clinical Dentistry and Research, 2026)
Background and Aim: This study evaluated the shearbond strength (SBS) of a universal resin cement to pre-milledtitanium surfaces using three different adhesive approaches.Materials and Methods: Forty-eight titanium specimens wereobtained from pre-milled titanium abutment blanks and equallydistributed into three experimental groups (n = 16) according tothe adhesive strategy: a dedicated metal primer (G-Multi Primer), atwo-bottle universal adhesive (Tokuyama Universal Bond II), and aone-bottle universal adhesive (Scotchbond Universal Plus). Prior tobonding, all surfaces were conditioned by airborne-particle abrasionusing 50 μm aluminum oxide particles. Resin cement cylinders wereprepared using a custom stainless-steel jig to ensure standardizeddimensions and positioning. The same self-adhesive dual-cure resincement (Maxcem Elite) was used for all specimens. Following 24hours of water storage at 37°C, immediate SBS was measured usinga universal testing machine at a crosshead speed of 1 mm/min.Fracture patterns after debonding were categorized as adhesive,cohesive, or mixed failures. Statistical evaluation included one-wayANOVA and Fisher’s Exact test at a significance level of 0.05.Results: Baseline surface roughness did not differ significantlyamong the experimental groups (p > 0.05). Airborne-particleabrasion increased the mean Ra value from 0.22 μm to 0.54 μm,with no significant differences among the groups after surfacetreatment (p > 0.05). Tokuyama Universal Bond II demonstratedthe highest mean SBS value (18.53 ± 2.45 MPa), followed byG-Multi Primer (17.32 ± 1.99 MPa) and Scotchbond UniversalPlus (16.67 ± 1.97 MPa). There were no significant differencesamong the adhesive systems (p = 0.057). Adhesive-type failurerepresented the most frequent fracture pattern across all groups,accounting for 62.5%–75% of failures. Cohesive fractures wereidentified only in the Tokuyama and G-Multi Primer groups.Conclusions: Both universal adhesives and dedicatedmetal primers demonstrated comparable immediate bondingperformance to titanium surfaces.